Comprehensive Review Of Analytical Methodologies For Gliclazide And Sitagliptin - Das, Sneha; D Patel, Bhoomi; Rathi, Sanjesh (Journal of Neonatal Surgery, 2025)
This comprehensive review examines and critically evaluates the analytical methodologies developed for Gliclazide and Sitagliptin, two widely used antidiabetic drugs. It provides a detailed analysis of method development and validation parameters, such as linearity, accuracy, precision, and robustness, as defined by international guidelines. The review study highlights the strengths and limitations of each method for quantifying these drugs in various matrices, including bulk drug, pharmaceutical formulations, and biological fluids. Special emphasis is placed on approaches which offers a systematic and risk-based framework for method development, ensuring a more robust and rugged analytical procedure. By synthesizing a vast body of literature, this review aims to provide researchers and analysts with critical insights to select the most appropriate and efficient analytical method for a given application. The insights gained from this review can guide future research in developing more sensitive, rapid, and eco-friendly analytical methods for the quality control and therapeutic monitoring of Gliclazide and Sitagliptin. This extensive study critiques Gliclazide and Sitagliptin's analytical methods, two popular antidiabetics. Novel techniques like Analytical Quality by Design (AQbD), which provides a systematic and risk-based framework for method development, are prioritised to provide a more robust analytical procedure. This review synthesises a large amount of knowledge to help researchers and analysts choose the best analytical approach for a specific application. The findings of this study can help create more sensitive, fast, and environmentally friendly analytical procedures for Gliclazide and Sitagliptin quality control and therapeutic monitoring. The review covers spectrometry, HPLC, UPLC, and their hyphenated variants like LC-MS and LC-ESI-MS-MS. It analyses worldwide guidelines-defined method development and validation characteristics including linearity, accuracy, precision, and robustness..